การศึกษาความต้องการในการฝึกอบรมล่ามในการช่วยเหลือและคุ้มครองสวัสดิภาพผู้เสียหายจากการค้ามนุษย์ในประเทศไทย - รัตนา แซ่เฮ้ง (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
This research aims to study the training needs for interpreters in settings of helping and providing protection to human trafficking victims in Thailand. This research is part of research project for interpreters in settings of helping and providing protection to human trafficking victims in Thailand. The objectives are to assess interpreters’ educational and training background, the interpreters attributes, and the training needs for interpreters in settings of helping and providing protection to human trafficking victims in Thailand as well as to compile the problems concerned and propose solutions. Questionnaire and interview are conducted with 20 relevant individuals consisting of 5 interpreters and 15 users including government officials, non-governmental organization (NGO) persons, interrogators, lawyers, and human trafficking victims who are the foreigners. It was found that all interpreters graduated with bachelor degree, but not in language program. Most of them do not have training background of interpreters in settings of helping and providing protection to human trafficking victims in Thailand. They all learned from the working experiences. Users and interpreters share similar view of interpreters attributes, except the native accent. The process of services involved in helping and providing protection to human trafficking victims is the most content demands for training course, in view of users and interpreters. Users top–ranked expected training content is terminology, while interpreters is code of ethics and guidelines to good practice. However, due to limited budget, there is lack of interpreters regular training course and training provider. Job and income insecurity also has impact on interpreters lack of motivation to attend in training course. Different view of interpreters expected attributes and training contents between users and interpreter is also another training challenge. To tackle these challenges, concerned agencies, particularly Thai government, should work with NGO to support interpreters regular training courses, to establish registered interpreter centers so as to guarantee job and income security for trained interpreters, to select experienced trainers, as well as to have the multidisciplinary team joining training program for their better understanding and awareness towards the important role of interpreters. These solutions would ensure the success of helping and providing protection to human trafficking victims in Thailand.